2010
DOI: 10.1523/jneurosci.4656-09.2010
|View full text |Cite
|
Sign up to set email alerts
|

Distinct Transcriptomes Define Rostral and Caudal Serotonin Neurons

Abstract: The molecular architecture of developing serotonin (5HT) neurons is poorly understood yet its determination is likely to be essential for elucidating functional heterogeneity of these cells and the contribution of serotonergic dysfunction to disease pathogenesis. Here, we describe the purification of postmitotic embryonic 5HT neurons by flow cytometry for whole genome microarray expression profiling of this unitary monoaminergic neuron type. Our studies identified significantly enriched expression of hundreds … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
138
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 99 publications
(148 citation statements)
references
References 71 publications
10
138
0
Order By: Relevance
“…However, the link between a neurochemical identity and a unique projection pattern remains an unresolved question in mice: in a recent study exploring neuropeptide expression in the raphe, none of the 12 peptides explored, including CRF, was found to be colocalized with 5-HT (Fu et al, 2010). In the future, more systematic analyses of the neurochemical/genomic identity of 5-HT neurons (Wylie et al, 2010) will be needed to extract precise neurochemical taxonomy of the dorsal and median raphe 5-HT neurons.…”
Section: Pet1-resistant 5-ht Neurons Define a Subsystem Embedded In Tmentioning
confidence: 98%
“…However, the link between a neurochemical identity and a unique projection pattern remains an unresolved question in mice: in a recent study exploring neuropeptide expression in the raphe, none of the 12 peptides explored, including CRF, was found to be colocalized with 5-HT (Fu et al, 2010). In the future, more systematic analyses of the neurochemical/genomic identity of 5-HT neurons (Wylie et al, 2010) will be needed to extract precise neurochemical taxonomy of the dorsal and median raphe 5-HT neurons.…”
Section: Pet1-resistant 5-ht Neurons Define a Subsystem Embedded In Tmentioning
confidence: 98%
“…Transcriptome analyses have mapped the differences in gene expression between and within the rostral and caudal clusters (Wylie et al, 2010;Okaty et al, 2015). In addition, the dorsal and median raphe serotonergic neurons display heterogeneity in their serotonin autoreceptor (Htr1a) and serotonin transporter (Sert; also known as Slc6a4) expression, electrophysiological properties, axonal morphology and susceptibility to neurotoxins (Mamounas et al, 1991;Crawford et al, 2010;Calizo et al, 2011;Kiyasova et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Boston naming test in a GWAS of the ageing brain and Wylie et al (Wylie et al, 2010) found a 13-fold increase in Diras2 expression in serotonergic neurons from the caudal hindbrain of mouse embryos, which could be indicative of a role of Di-ras2 in the regulation of the caudal serotonergic system. The latter is intriguing, as serotonin has been found to be critically involved in brain development and to impact on ADHD-related traits such as aggression and impulsivity (Azmitia, 2001;Halperin et al, 1994;Lucki, 1998).…”
Section: Diras2 Polymorphism Has a Functional Impact In Adhd L Grünewmentioning
confidence: 96%